Vibration analysis of corrugated beams: The effects of temperature and corrugation shape. (January 2016) - Robin, G.; Jrad, M.; Mathieu, N.; Daouadji, A.; Daya, E.M.
Highlights: Analytical approach for studying nonlinear dynamic behavior of corrugated beams. Application: the effect of the temperature. Response of clamped–clamped BC is more stable than one of simply supported. Increase of the amplitude delayed the jump phenomenon. Decrease of the period delayed the jump phenomenon. Abstract: This paper deals with the vibration analysis of corrugated beams under large amplitude displacements and temperature variations. The dynamic response depends on the shape, the period and the amplitude of the corrugations as well as on the temperature variations. These different parameters were taken into account using a homogenization process. We coupled the harmonic balance method and the Galerkin technique to derive a frequency amplitude equation, which includes the corrugation shape and temperature. Finally, the influence of different shapes of corrugation (sinusoidal, triangular and square) on the nonlinear vibration response of a corrugated beam was compared to results obtained for a planar beam.